2022
DOI: 10.1111/fwb.13951
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic dynamics during colonisation and establishment of an obligate parthenogenetic Daphnia pulex population in a small lake of a continental archipelago

Abstract: Population genetic diversity and structure are known to influence successful colonisation and establishment of a population in a novel habitat. However, our understanding of actual population genetic changes in the early stage of colonisation and detailed time‐series of genetic changes during the establishment of a new population is still limited due to the difficulty of making long‐term direct observations of a colonising population. Using a paleolimnological approach, we revealed the long‐term genetic dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Genetically isolated genotypes of Daphnia cf. pulex sensu Hebert (1995) are often found in single lakes (Crease et al., 1989; Hebert & Crease, 1980, 1983; Otake et al., 2022; So et al., 2015). Hebert and Crease (1980) questioned whether the co‐occurrence of obligate asexual genotypes is long‐lasting and, if so, how such a paradoxical situation is maintained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically isolated genotypes of Daphnia cf. pulex sensu Hebert (1995) are often found in single lakes (Crease et al., 1989; Hebert & Crease, 1980, 1983; Otake et al., 2022; So et al., 2015). Hebert and Crease (1980) questioned whether the co‐occurrence of obligate asexual genotypes is long‐lasting and, if so, how such a paradoxical situation is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that multiple genotypes of asexual D. cf. pulex are often found in single lakes (Otake et al, 2022;So et al, 2015). Such lakes provide an excellent opportunity to determine whether these different asexual genotypes can coexist over long periods of time, and what mechanisms enable long-term coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…By extending the model to incorporate spatial dynamics, it may be possible to examine whether the intraspecific difference in diapausing strategy can affect migration and range expansion. In Lake Fukami-ike, paleolimnological and population genetic analyses of diapausing eggs revealed that Jpn2C was established earlier than Jpn1A-C2T2 [ 45 ]. Further evolutionary and genetic research can contribute to our understanding of evolutionary dynamics with intraspecific interaction and spatial competition–colonization trade-off [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…These clones were identified genetically based on mitochondrial markers in ND5 with primers ND5 f21 and ND5 r1046 [41] and the control region of mitochondrial DNA with primers IAIT fw and IAIT rv1 [41,47]. Full details of these genetic identification processes are described in our previous study [45]. We used seven clones of each genotype, Jpn1-C2T2 and Jpn2C; thus, we used 14 clones in total.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation